Persepsi Sastra Dalam Nilai Humanisme pada Kumpulan Puisi Tahta Sungkawa Karya Binhad Nurrohmat - Ermaniah, Ermaniah; Wardiah, Dessy; Hetilaniar, Hetilaniar (Institut Teknologi Pendidikan Indonesia, 2022)
This study aims to describe the reception of literature in terms of humanism values in the collection of poems by Binhad Nurrohmat's Throne of Sungkawa. The problems revealed in the research regarding the value of humanism in the five poems with the theme of human life with all aspects of the problem. Sources of informants came from the academic level of PGRI Palembang University students in 2018, 2019, and 2020 who had taken poetry study/appreciation courses. The research method is descriptive qualitative, with data collection techniques using questionnaires and interviews. Data analysis is carried out by presenting data, with analysis in tabular form. The results of the study can be concluded thatstudents who understand the reception of the themes of the five poems are; the journey of human life in the world until it is time to prepare for death. Reception of tones glorifies lower tones with a plot of sadness. Feelings/feelings in the five poems namely; feelings/feelings associated with the soul of the author with a religious background. Reception of the message, namely; do not feel that this world is everything. The five poems created by the author present human values for humans to live their lives in a positive direction.